Acompanhamento fenológico de espécies arbóreas e arbustivas em um fragmento de Caatinga no Município de Mossoró, RN - Quirino, Natália Isabel Lopes (Universidade Federal Rural do Semi-Árido, 2021)
Phenology studies the different phases of plant growth and development, establishing the period of occurrence and its characteristics, contributing to the understanding of the processes that occur in a forest area and management effectiveness. The aim of this work was to determine the phenological pattern of eight tree and shrub species in a patch of caatinga at the Rafael Fernandes Experimental Farm, located in the municipality of Mossoró - RN, Brasil, as well as to evaluate the correlation between phenophases and precipitation and to calculate synchrony indices of the events for the population and individuals of each species. The phenological data were collected over two years and ten months, in the period 2017 to 2020 and refer to the leaf fall, leaf flushing, flowering and fruiting cycles. Ten individuals were selected for each species (totaling 80 trees), with the inclusion criterion the apparent vigor of the trees and a minimum distance of 20 m. The species monitored were: Pityrocarpa moniliformis (Benth.) Luckow and RW Jobson, Cenostigma pyramidale (Tul.) Gagnon and GP Lewis, Commiphora leptophloeos (Mart.) JB Gillett, Piptadenia stipulacea (Benth.) Durke, Manihot carthagenensis subsp. glaziovii (Mull. Arg.) Allem, Bauhinia cheilantha (Bong.) Steud, Cordia glazioviana (Taub.) Gottshling & JS Mill. and Jatropha mollissima (Pohl) Baill. In the observations made at 14-day intervals, the vegetative phenophases were registered in percentage and the reproductive in relation to the real amount of fruits and flowers. Analysis of the intensity of the phenophases followed the method proposed by Fournier. Precipitation data for the region were obtained from the meteorological station records of the Rafael Fernandes Experimental Farm. After data processing, precipitation graphs were crossed with phenophase graphs. The synchrony indices were calculated using the Augspurger formulas. The information obtained reveals that all species presented a well-defined phenological calendar regarding the occurrence of phenophases. There was a clear dependence on rainfall variability, as most species began leaf fall in the month of June, a period of rainy decline in the area (dry season). New leaves were issued as the rainy season established itself in the region, with higher peaks between the months of January and February. The reproductive phases varied with some species activating reproduction mechanisms during the rainy period (J. mollissima and M. carthagenensis), while others reached high production of flowers and fruits during the dry period (C. glazioviana and P. stipulacea). The synchrony between individuals of the populations of different species was low, indicating that, with the exception of the species C. glazioviana, the availability of floral resources and fruits for the fauna occurred at different times
Keywords: Fenologia; Nordeste; Espécie nativa; Caatinga. Semiárido; Phenology; Northeast; Native species; Caatinga; Semiarid; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL